(untitled) (Marketing Journal, 2025)
This article examines the key directions that determine the efficiency of the transport system, the interrelation between the concepts of the transport complex, transport system, and transport infrastructure. It also presents comparative evaluations of dif ferent modes of transport based on key factors influencing transport choice. The specific features of optimizing cargo delivery costs are highlighted, and the main tasks for improving the efficiency of the transport system are identified.